Effect of eplerenone in patients with heart failure and reduced ejection fraction: potential effect modification by abdominal obesity. Insight from the EMPHASIS‐HF trial. (16th March 2017) - Olivier, Arnaud; Pitt, Bertram; Girerd, Nicolas; Lamiral, Zohra; Machu, Jean‐Loup; McMurray, John J.V.; Swedberg, Karl; van Veldhuisen, Dirk J.; Collier, Timothy J.; Pocock, Stuart J.; Rossignol, Patrick; Zannad, Faiez; et al.
Abstract: Aims: An excessive production of aldosterone influences outcome in patients with heart failure (HF) and in obese patients. Findings from laboratory studies suggest that chronic aldosterone blockade maybe more beneficial in abdominally obese HF‐prone rats. In the current study, we investigated if the clinical response to a mineralocorticoid receptor antagonist in mildly symptomatic HF patients varied by abdominal obesity. Methods and results: A total of 2587 NYHA class II, reduced ejection fraction HF (HFrEF) patients enrolled in the EMPHASIS‐HF trial were randomly assigned to eplerenone and placebo. In this post hoc analysis, patients were categorized according to waist circumference (WC) (normal if WC < 102 cm in men and < 88 cm in women; abdominal obesity if WC ≥ 102 cm in men and ≥ 88 cm women). The potential statistical interaction between the treatment and WC was assessed on the primary endpoint of death from cardiovascular causes or hospitalization for HF and other secondary endpoints. Over a median follow‐up of 21 months, a significant benefit of eplerenone for the primary outcome was noted in both normal [hazard ratio (HR) 0.77, 95% confidence interval (CI) 0.61–0.98, P = 0.03] and increased (HR 0.48, 95% CI 0.37–0.63, P < 0.0001) WC subgroups, but the latter patients appeared to receive greater benefit than patients with normal WC ( P for interaction = 0.01). This suggests a significant quantitative (treatment effect varies in magnitude by subgroup, but is always in same direction) rather than a qualitative interaction (direction of the treatment effect varies by subgroup) between eplerenone and WC in the adjusted analysis. Mean doses of eplerenone, blood pressure and serum potassium changes and adverse events were similar between WC subgroups. Conclusion: In EMPHASIS‐HF, eplerenone improved outcomes in HFrEF patients with and without abdominal obesity, although the benefit appeared to be more pronounced among those with abdominal obesity. The findings are potentially hypothesis generating and need to be replicated in other HFrEF populations.